Code Switching in EFL Students’ Proposal Seminar Presentation - Al Inayah Alfathia Amamah; Suleman Bouti; Fahria Malabar (TRANS-KATA: Journal of Language, Literature, Culture and Education, 2021)
In academic situations, especially in proposal seminar presentations, code switching is generally used by the presenter and the audience also by all elements in the presentation for the different activities and different purposes. It gives a chance to them to communicate with each other by using their first language and foreign language. This qualitative study aims to explain the types of code-switching and the factors causing the students to use code-switching in their proposal seminar presentations. The subjects were four EFL students who were presenting their research proposal. An observation technique was used to retrieve the main data, which is the students’ proposal seminar presentation. Moreover, this study employed an interview technique to obtain the supporting data about factors affecting the students in utilizing code-switching. The theory about  types and factors of code-switching was used in this research to analyze the data. The results find four types of code-switching. Those four types are Intra-sentential switching, inter-sentential switching, establishin continuity switches, and tag switching. The result also shows that several factors affect students using codeswitching, such as the real lexical need, quoting somebody else, interjection or inserting sentence fillers or sentence connectors, being emphatetic about something clarifying the speech content for the interlocutor. Based on the finding, all types of code-switching are found in this research, and there are only six out of ten factors found in this research.